Digital Strain and its Impact on Visual and Auditory Health in an Online Learning Environment: A Cross-sectional Study - Ramadevi Kumar; Gothainayagi Arumugam; Rangeela Ravi; Samuraj Nehru; Sasirekha Nedunchezian; Sevvanthi Kumar (National Journal of Community Medicine)
Background: During the COVID-19 pandemic, concerns extended beyond respiratory health to include visual and auditory well-being in school-aged children. This study aimed to assess the prevalence and risk factors of digital device-related visual and auditory strain in children.